Clothing Optional?: Nudity and the Law of the Australian Beach - Theodore Bennett (Bond Law Review)
This article comprises the first detailed legal analysis of nudity on the Australian beach. It provides an overview of the formal law around public nudity on Australian beaches and unpacks both the cultural significance and practical operation of regulation within this context. It begins by demonstrating how the Australian beach is a particularly dense nexus of cultural meaning and significance, within which general cultural anxieties about public nudity are amplified. It then sets out the formal legal apparatus that performs the regulatory work that responds to these anxieties, including State/Territory offences relating to public exposure, public behaviour and bathing dress. However, the law ‘in the books’ about beach nudity diverges in significant ways from the law ‘in action’, and this analysis unpacks the practical side of the law of the Australian beach in terms of policing discretion, the application of legal standards of decency and propriety, and social patterns of nude beach use. The formal designation of certain spaces by some States/Territories as ‘free beaches’— where it is not against the law to be nude — is argued to constitute the symbolic containment, rather than endorsement, of public nudity.